2018
DOI: 10.1002/er.4267
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of energy efficiency measures in the Swiss chemical and pharmaceutical industry

Abstract: Summary Energy efficiency improvement is an effective way of reducing energy demand and CO2 emissions. Although the overall final energy savings potential in chemical industry has been estimated in a few countries, energy efficiency potentials by concrete measures applicable in the sector have been scarcely explored and their associated costs are hardly analyzed. In Switzerland, the production of chemicals and pharmaceuticals exceeds all other industrial sectors in terms of energy use and CO2 emissions, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…on the industrial sector, the year of implementation, the annual final energy savings by energy carrier and in many cases both total and additional investment costs. Utilization of the economic data for analyzing the cost-effectiveness of the implemented measures is outside the scope of this study but can be found in [19,24,51,54,57,58].…”
Section: Data Analysis Of Swiss Companies With Target Agreementsmentioning
confidence: 99%
“…on the industrial sector, the year of implementation, the annual final energy savings by energy carrier and in many cases both total and additional investment costs. Utilization of the economic data for analyzing the cost-effectiveness of the implemented measures is outside the scope of this study but can be found in [19,24,51,54,57,58].…”
Section: Data Analysis Of Swiss Companies With Target Agreementsmentioning
confidence: 99%
“…Studies have addressed the energy and cost savings coming from improving energy efficiency in electric drives [39]. Further, studies have addressed energy use, and energy savings, together with emission analysis and cost-effectiveness of EMS, with focus on different type of industries: to name a few, Malaysian rubber producing and cement industries [40], [41], garment industrial building in Bangladesh [42], cement manufacturing [43], Swiss chemical and pharmaceutical industry [44], and petrochemical one [45]. Further, experience in US case studies has been reported, by looking at retrofitting standard efficiency motors with higher efficiency ones [46].…”
Section: Literature Background and Research Gapsmentioning
confidence: 99%
“…On the other hand, scientific literature has also conducted cost-benefit analyses of EEMs in EMS, nevertheless without sufficient detail over the specific EEMs to be considered at operational level [13]. Further, despite the relevance of cost-benefit analysis, as authors note [10], [14], economics represents an important barrier, but not necessarily the main one [15] and the knowledge itself of financial and economic performance indicators [16], [17], if not complemented by a thorough analysis of the impacts on production, does not offer the full picture [18].…”
Section: Introductionmentioning
confidence: 99%
“…18 Stougie et al compared exergy, energy, and economic analysis methods to assess the power generation from fossil and renewable energy sources and indicated that environmental and economic sustainability assessments strongly depend on the models, weighting factors, and energy price but exergy analysis does not. To obtain quantified performance indicators in the system performance evaluation stage, different types of energy on the input side and output side of the energy system should be summed together.…”
mentioning
confidence: 99%
“…Zuberi (2019) discussed the economic cost of energy efficiency and indicated that the integrated consideration of energy resources and economic cost provides useful insights into energy system design. 18 Stougie et al compared exergy, energy, and economic analysis methods to assess the power generation from fossil and renewable energy sources and indicated that environmental and economic sustainability assessments strongly depend on the models, weighting factors, and energy price but exergy analysis does not. 19 A theoretical analysis method for the energetic and exergy efficiency of an integrated energy system was introduced by Huang et al in 2018, which indicated that the energy and exergy analysis results of a multi-energy system are different in many situations.…”
mentioning
confidence: 99%